Diagnosis of university archives: a contribution to records management at the Universidade Federal de Pernambuco - Barbosa, Beatriz de Oliveira; Santos, Thais Helen do Nascimento (Ciência da Informação em Revista, 2024)
Higher education institutions produce and accumulate vast documentation, whether administrative and legal, scientific productions and historical documentation. Therefore, it is essential that such documents are managed properly. To this end, records management procedures must be applied, as it adds several positive factors to the management of an institution’s documentation. Thus, the first stage of records management is carrying out an archival diagnosis, an activity used to obtain in-depth knowledge about the archival unit. In this context, the objective of this research is to carry out an archival diagnosis of the archives of the Centro de Artes e Comunicação and the Centro de Filosofia e Ciências Humanas of the Universidade Federal de Pernambuco, with the aim of identifying points that can be improved. Regarding the methodology, this is an exploratory and descriptive study, with a quantitative-qualitative approach. Data collection was carried out through direct observation, with the support of an observation script, this being the diagnosis methodology of Marilena Leite Paes, chosen because it covers the physical part, as well as informational elements of a file, thus allowing a more complete analysis of the archival unit. As a result, points for improvement in the archive collections studied were identified, observing the need for adequate treatment of archival documentation present in the collections, following records management precepts.